On Homogeneous Cubic Equation with Four Unknowns: On Homogeneous Cubic Equation with Four Unknowns - Kumar, Sharadha (Asian Journal of Mathematical Sciences(AJMS), 2018)
The cubic diophantine equation with four unknowns given by ï€¨ ï€© ï€¨ ï€© 3 3 2 2 x ï€« y ï€« x ï€« y x ï€ y ï€½16zw is analyzed for its non-zero distinct integer points on it. Different patterns of integer points for the equation under consideration are obtained. A few interesting relations between the solutions and special number patterns namely Polygonal number, Gnomonic number, Star number and Pronic number are presented.